2009
DOI: 10.1371/journal.pone.0005621
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Length Dependence of DNA Looping in Transcriptional Regulation

Abstract: In many cases, transcriptional regulation involves the binding of transcription factors at sites on the DNA that are not immediately adjacent to the promoter of interest. This action at a distance is often mediated by the formation of DNA loops: Binding at two or more sites on the DNA results in the formation of a loop, which can bring the transcription factor into the immediate neighborhood of the relevant promoter. These processes are important in settings ranging from the historic bacterial examples (bacter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
160
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(177 citation statements)
references
References 104 publications
(204 reference statements)
17
160
0
Order By: Relevance
“…The loop assistance we observed in vivo is consistent with the distance-shortening effect of nested loops. The statistical weight of a looped species is directly related to the factor j LOOP , the effective concentration of one looping site relative to the other, which quantitates the DNA-tethering effect (24,51). We have shown that j LOOP for LacI and CI loops over the 600-to 10,000-bp range in E. coli cells is roughly inversely proportional to the DNA separation (24).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The loop assistance we observed in vivo is consistent with the distance-shortening effect of nested loops. The statistical weight of a looped species is directly related to the factor j LOOP , the effective concentration of one looping site relative to the other, which quantitates the DNA-tethering effect (24,51). We have shown that j LOOP for LacI and CI loops over the 600-to 10,000-bp range in E. coli cells is roughly inversely proportional to the DNA separation (24).…”
Section: Discussionmentioning
confidence: 91%
“…S4B). j LOOP is the effective concentration of one site on the DNA relative to another site on the same DNA molecule, and is a critical parameter in determining loop efficiency (51). From this estimate of j LOOP for a 1,400-bp loop, and our previous measurements of the dissociation constants for LacI at O1, it is possible to calculate F Lac = 0.82 for the 1,400-bp Oid-O1 loop (24) (SI Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…for K d by estimating the concentration at which the two peaks have equal weight (and thus, the concentration where either of these two states is equally likely). More formally, we used a statistical mechanical model of binding (19,20) to extract the relevant K d values taking into account the binding histograms over the entire concentration range. In this case, for the 12RSS site, we found K d = 13.9 ± 4.7 nM, which is within error of a previously reported value of 14.5 ± 2.4 nM (21) and less than the only other measured value of K d = 25.0 ± 5.0 nM derived from bulk experiments (22).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicate that LacI looping with short DNA tethers (<500 bp) is less efficient in vitro than in vivo. To test whether this difference holds for longer DNA tethers, we examined LacI looping in single molecules by TPM (9,(30)(31)(32), where looping of a DNA molecule attaching a bead to a surface can be detected as a restriction in the Brownian motion of the bead (Fig. 5A).…”
Section: Effect Of Separation On Long-range Looping By λ Repressor Inmentioning
confidence: 99%
“…Measurements of j LOOP for protein-induced looping give a similar picture. Most studies have focused on linear tethers <500 bp, finding variable j LOOP values generally below 100 nM (9). Lower j LOOP values are seen at longer separations: ∼18 nM for Cre DNA recombination at 3,000 bp (15), whereas LacI DNA binding cooperativity was undetectable at Significance Proteins bound to DNA often interact with proteins bound elsewhere on the same DNA to regulate gene expression.…”
mentioning
confidence: 99%